2021
DOI: 10.1037/cfp0000162
|View full text |Cite
|
Sign up to set email alerts
|

“Life is already hard enough”: Lesbian and gay adoptive parents’ experiences and concerns after the 2016 presidential election.

Abstract: The 2016 U.S. presidential election was an especially difficult election for many Americans, particularly individuals with one or more marginalized identities. This qualitative study explores the experiences of sexual minority adoptive parents (n = 50), many of whom were members of multiracial families. Parents completed an online survey 2-3 weeks after the November 2016 presidential election, and 2.5 months later (1-2 weeks after the January 2017 inauguration). Through an integrated minority stress and inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Although the consequences of the Parental Rights in Education Act were still uncertain, insomuch as the participants were surveyed during the summer, the fact that it was accompanied by an increasingly hostile sociopolitical context across the state was enough to create fear, anger, disbelief, and sadness. Such emotional responses echo prior work on how LGBTQ+ parents responded to the election of President Trump (Gabriele-Black et al, 2021), but differ in that the parents in this study were generally not surprised by the Parental Rights in Education Act, in that it fell in line with many other recent legislative attacks on LGBTQ+ people and families (Abreu et al, 2021a). It also differs in that, contrary to prior work on LGBTQ+ people’s responses to anti-LGBTQ+ legislation, parents’ concerns were mostly centered on their children, and, secondarily, their families: indeed, the Parental Rights in Education Act is centrally focused on the daily learning environment of children (Kline et al, 2022).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Although the consequences of the Parental Rights in Education Act were still uncertain, insomuch as the participants were surveyed during the summer, the fact that it was accompanied by an increasingly hostile sociopolitical context across the state was enough to create fear, anger, disbelief, and sadness. Such emotional responses echo prior work on how LGBTQ+ parents responded to the election of President Trump (Gabriele-Black et al, 2021), but differ in that the parents in this study were generally not surprised by the Parental Rights in Education Act, in that it fell in line with many other recent legislative attacks on LGBTQ+ people and families (Abreu et al, 2021a). It also differs in that, contrary to prior work on LGBTQ+ people’s responses to anti-LGBTQ+ legislation, parents’ concerns were mostly centered on their children, and, secondarily, their families: indeed, the Parental Rights in Education Act is centrally focused on the daily learning environment of children (Kline et al, 2022).…”
Section: Discussionsupporting
confidence: 77%
“…During the campaigns associated with marriage amendments in the United States, lesbian, gay, bisexual, and queer people reported hopelessness, anger, fear, and distress (Flores et al, 2018), although some also maintained hope that legislative setbacks would be overcome and equality would prevail (Rostosky et al, 2010). Anti-LGBTQ+ legislation as it relates to LGBTQ+ people’s mental health has been studied most recently in relation to Donald Trump’s presidential election and administration (Brown & Keller, 2018; Gabriele-Black et al, 2021; Gonzalez et al, 2022; Price et al, 2021). Trump implemented many policies that instantiated and reinforced LGBTQ+-related discrimination, creating minority stress for LGBTQ+ people, which manifested as increased symptoms of anxiety and depression; specific worries about employment protections, healthcare access, and the rollback of civil rights; as well as a general sense of unease, fear, and lack of safety (Brown & Keller, 2018; Gabriele-Black et al, 2021; Price et al, 2021; Radis & Nadan, 2021).…”
Section: Anti-lgbtq Legislation and Lgbtq Parent Family Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that LG parents were more likely than heterosexual parents to talk to school administrators if their children were being victimized (Goldberg & Garcia, 2020). In addition to advocating for greater inclusivity and acceptance within their children's schools, LGBTQ parents also talk to their children about heterosexism and homophobia and also teach them to advocate for themselves (Gabriele‐Black et al, 2021; Ollen & Goldberg, 2015).…”
Section: Lgbtq Parent Familiesmentioning
confidence: 99%
“…Structural stigma in the form of public policies and associated political discourse impacts the social relationships of LGBTQ + people, contributing to relationship strain and loneliness (Anderson et al, 2020 ; Doyle & Molix, 2015 ; Gabriele-Black et al, 2021 ), lower relationship satisfaction with significant others (Frost & Fingerhut, 2016 ), and increased arguments with co-workers and family members (Brown & Keller, 2018 ). However, when surrounded by supportive others, experiences of structural stigma can lead to deepened feelings of closeness and openness to discuss one’s sexual orientation (Maisel & Fingerhut, 2011 ), and increased resilience within LGBTQ + communities via increased community contact (Russell & Richards, 2003 ).…”
Section: Introductionmentioning
confidence: 99%